First case report of bacteremia due to 'Campylobacter-like organism 3'. (January 2016) - Nakamura, Itaru; Ohkusu, Kiyofumi; Nakagami, Yoshihiro; Tachibana, Masaaki; Matsumoto, Tetsuya
Highlights: A case of bacteremia caused by Campylobacter-like organism 3 (CLO-3) is reported. CLO-3 has been reported previously, without the formal definition of a species. CLO-3 is known to cause enterocolitis. The isolate was identified as CLO-3 by analysis of the 16S rRNA and hsp60 genes. CLO-3 may represent another emerging cause of Helicobacter-induced bacteremia. Summary: A case of bacteremia caused by a rare Helicobacter species, Campylobacter-like organism 3 (CLO-3), in a 75-year-old man with prostate cancer and an indwelling urethral catheter for urinary retention, is reported. Oral levofloxacin (500 mg per day) was effective, although the results of antimicrobial susceptibility testing were unknown. Non-film-like, small, clear colonies were isolated on blood agar after 72 h of microaerobic incubation at 37 °C. Biochemical testing indicated that the isolates were catalase-positive, negative for nitrate reduction and urease activity, and positive for indoxyl acetate hydrolysis. The isolate was identified as CLO-3 by sequence analysis of the 16S rRNA and hsp60 genes. Although CLO-3 is known to cause enterocolitis, bacteremia due to CLO-3 has not been described. There have been an increasing number of reports of bacteremia caused by Helicobacter cinaedi and Helicobacter fennelliae, which were first reported as CLO-1 and CLO-2, and CLO-3 may represent another emerging cause of Helicobacter-induced bacteremia.